(untitled) (Architecture Image Studies, 2025)
This study conducts a comprehensive bibliometric analysis to map the evolution, intellectual structure, and research frontiers of Digital Governance (DG) from 2014 to 2025. Using the Scopus database and the Bibliometrix package in R, a total of 270 journal articles were analyzed following the PRISMA protocol. The results reveal a steady growth in DG publications, particularly after 2020, driven by global digital transformation initiatives and the expanding role of artificial intelligence in governance. Thematic and co-occurrence analyses identify three dominant clusters: (1) institutional and administrative transformation in public governance, (2) technological and ethical innovation, including AI, data ethics, and algorithmic accountability, and (3) sustainability-oriented digital governance. Network analyses highlight China, the United States, and the United Kingdom as leading contributors with strong transnational collaboration, while emerging economies such as Indonesia, India, and Brazil are increasingly active in this field. The study concludes that DG has evolved into a mature, interdisciplinary domain that bridges governance, technology, and society. Future research should focus on exploring institutional sensemaking, policy learning, and adaptive governance to better understand how digital transformation reshapes public value creation, accountability, and inclusivity across diverse contexts.